2022
DOI: 10.1186/s42358-022-00257-0
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of systemic lupus erythematosus on sexual function in women: an updated meta-analysis based on cross-sectional studies

Abstract: Background Systemic lupus erythematosus (SLE), a chronic systemic autoimmune disease, often affects different organs and tissues. It can be effectively managed using drugs; however, attention should be paid to the patient’s quality of life. This study aimed to evaluate the effect of SLE on female sexual function based on current literature. Methods The PubMed, Embase, and Cochrane Library databases were searched for eligible studies published up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Despite the fact that life expectancy is generally favorable ( 41 , 42 ), racial and ethnic minority groups experience more severe outcomes ( 43 ), and SLE can dramatically affect all areas of a patient’s life, including physical health, mental health, and social relationships ( 44 ). Recent research has highlighted poor physical and mental health related quality of life in patients with SLE, with literature indicating that SLE can cause pain and fatigue ( 45 , 46 ), poor sleep quality ( 47 ), feelings of fear, anguish, and social exclusion ( 48 ), decreased sexual function ( 49 ), concerns around fertility and reproductive health in women ( 50 ), and challenges around economic costs, status, and employment ( 51 ). In addition, quality of life may be affected differently at different phases of disease ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that life expectancy is generally favorable ( 41 , 42 ), racial and ethnic minority groups experience more severe outcomes ( 43 ), and SLE can dramatically affect all areas of a patient’s life, including physical health, mental health, and social relationships ( 44 ). Recent research has highlighted poor physical and mental health related quality of life in patients with SLE, with literature indicating that SLE can cause pain and fatigue ( 45 , 46 ), poor sleep quality ( 47 ), feelings of fear, anguish, and social exclusion ( 48 ), decreased sexual function ( 49 ), concerns around fertility and reproductive health in women ( 50 ), and challenges around economic costs, status, and employment ( 51 ). In addition, quality of life may be affected differently at different phases of disease ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large UKCTOCS cohort of around 4000 postmenopausal women uncovered the burden of poor sexual health and its impact on the family, including mental and emotional well-being and this burden is bigger in AIRDs [47]. A recent metaanalysis concluded that the female sexual function index (FSFI) was significantly lower in patients with SLE and this was augmented by depression, disease activity and severity [48]. An interesting possibility of autoimmune oophoritis in SLE is also suggested by some researchers as a cause of estrogen decline, premature menopause and sexual ill-health, eventually contributing to a low QoL [49,50].…”
Section: Aging and Sexual Healthmentioning
confidence: 99%